Leaving coal unburned: Options for demand-side and supply-side policies - Kim Collins; Roman Mendelevitch (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Climate policy consistent with the 2°C target needs to install mechanisms that leave most current coal reserves unburned. Demand-side policies have been argued to be prone to adverse carbon leakage and "green paradox" effects. A growing strain of literature argues in favor of supply-side policies in order to curb future coal consumption. Various concepts with analogies in other sectors are currently discussed. Future empirical research on both demand- and supply-side policy is vital to be able to design efficient and effective policy instruments for climate change mitigation.
Keywords: 330